The differential impact of employment in agriculture on wages for rural and non-rural Palestine - Yousef Daoud; Belal Fallah (IZA Journal of Labor & Development, 2016)
This paper investigates the differential impact of employment in agriculture on rural and non-rural wages using the quarterly labor force survey (LFS) collected by the Palestine Central Bureau of Statistics (PCBS). We estimate the wage equation for rural and non-rural workers controlling for structural, socioeconomic, and political factors. The results suggest that employment in agriculture lowers the average wage by a range from 26 to 34 % for the non-rural population and 30-37 % for rural population. Meanwhile, Israeli closures tend to raise the probability of selecting agriculture as a sector for employment. Among other findings, the results also show that returns to education are lower for rural workers than for non-rural workers.
Keywords: R11; J30; J61; J01; 330; Labor supply; Labor demand; Commuting; Wage differential